Self-directed learning research and its impact on educational practice - Mentz, Elsa (NWU Self-Directed Learning Series, 2020)
This scholarly book is the third volume in an NWU book series on self-directed learning and is devoted to self-directed learning research and its impact on educational practice. The importance of self-directed learning for learners in the 21st century to equip themselves with the necessary skills to take responsibility for their own learning for life cannot be over emphasised. The target audience does not only consist of scholars in the field of self-directed learning in Higher Education and the Schooling sector but includes all scholars in the field of teaching and learning in all education and training sectors. The book contributes to the discourse on creating dispositions towards self-directed learning among all learners and adds to the latest body of scholarship in terms of self-directed learning. Although from different perspectives, all chapters in the book are closely linked together around self-directed learning as a central theme, following on the work done in Volume 1 of this series (Self-Directed Learning for the 21st Century: Implications for Higher Education) to form a rich knowledge bank of work on self-directed learning.